A Combinational Sequence Duty Ratio Control of SPV Fed Variable Speed Induction Motor Drive Using Field Oriented Control. Issue 11 (21st July 2022) - Narendra, Ankireddy; Naik N, Venkataramana; Panda, Anup Kumar
Abstract: This paper emphasizes the performance of solar photovoltaic (SPV) fed field-oriented control (FOC) based induction motor drive (IMD) using combinational sequence (CBS) based duty ratio control (DRC). The low-efficiency problem of SPV panels is resolved with the help of the maximum power point tracking (MPPT) algorithm. Here, the incremental conductance (INC) algorithm and the boost converter extract maximum power from the SPV system. Moreover, the control of IMD is performed using FOC and a 2-level 3-Φ inverter. Furthermore, the reduction voltage/current total harmonic distortion (THD) in IMD is achieved using PWM techniques. Here, the proposed CBS-DRC is a combination of switching sequences in every sector region. However, CBS's operation selects the less area of root mean square (RMS) of stator flux ripples (SFRs) to improve the voltage/current profile of the 3-Φ IMD. Consequently, the reduced torque ripple and speed variations are achieved with the proposed CBS-DRC compared to 0127 sequences. However, the switching sequences are implemented in real-time using the DSPACE DS-1104 controller. Also, a comparison of the overall performance of IMD using 0127 sequence DRC and the proposed CBS-DRC at various loading conditions is disclosed.